2011
DOI: 10.1038/bjc.2011.492
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CIP2A in renal cell carcinomas correlates with tumour invasion, metastasis and patients’ survival

Abstract: Background:Cancerous inhibitor of protein phosphatase 2A (CIP2A) drives cellular transformation. The objective of this study was to detect the potential effects of CIP2A in renal cell carcinomas (RCCs).Methods:A total of 107 RCC patients were involved in the study. Cancerous inhibitor of protein phosphatase 2A expression was investigated by real-time PCR and immunohistochemistry. In vitro, we examined the expression of CIP2A and c-Myc and tested the migration and invasion capability of A498 and KRC/Y cells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 36 publications
5
47
0
Order By: Relevance
“…When PP2A is inhibited by CIP2A, PP2A-mediated dephosphorylation of these oncoproteins is blocked, thus promoting anchorage-independent cell growth and in vivo tumor formation. CIP2A functions as an oncoprotein that promotes proliferation and aggressiveness of several cancer types including head and neck squamous cell carcinoma, oral squamous cell carcinoma, esophageal squamous cell carcinoma, colon, gastric, breast, prostate, tongue, lung, and cervical cancer, as well as acute myeloid leukemia (6,(9)(10)(11)(12). In addition, aberrant expression, mutations, and somatic alterations of the PP2A scaffold and regulatory subunits are frequently found in human breast, lung, colon, and skin cancers (13).…”
Section: Introductionmentioning
confidence: 99%
“…When PP2A is inhibited by CIP2A, PP2A-mediated dephosphorylation of these oncoproteins is blocked, thus promoting anchorage-independent cell growth and in vivo tumor formation. CIP2A functions as an oncoprotein that promotes proliferation and aggressiveness of several cancer types including head and neck squamous cell carcinoma, oral squamous cell carcinoma, esophageal squamous cell carcinoma, colon, gastric, breast, prostate, tongue, lung, and cervical cancer, as well as acute myeloid leukemia (6,(9)(10)(11)(12). In addition, aberrant expression, mutations, and somatic alterations of the PP2A scaffold and regulatory subunits are frequently found in human breast, lung, colon, and skin cancers (13).…”
Section: Introductionmentioning
confidence: 99%
“…(14) This work investigated the correlation of the UHRF1 DNA level in plasma with clinical characteristics of breast cancer and its clinical significance in breast cancer diagnosis.…”
mentioning
confidence: 99%
“…More recently, CIP2A expression has been found to be associated with the invasive function of fibroblast-like synoviocytes and synovial hyperplasia in rheumatoid arthritis (19). In addition, it has been reported that CIP2A immunostaining level positively correlated with metastasis in renal cell carcinomas (6). More recently, In addition, Zhai et al (20) found that CIP2A was overexpressed in osteosarcoma tissues, and that CIP2A depletion attenuated cell proliferation and invasion.…”
Section: A B C Discussionmentioning
confidence: 98%
“…CIP2A is a widespread oncogenic factor in human neoplasms (4)(5)(6)(7)(8)(9)3). Similar to the Ras oncogene, CIP2A is required for anchorage-independent cell growth and malignant transformation of human cells (4).…”
Section: A B C Discussionmentioning
confidence: 99%
See 1 more Smart Citation